Christian Fundamentalism in America: A Cultural History, by David S. New - Lamoreaux, Jason (Religious Studies and Theology, 2016)
Christian Fundamentalism in America: A Cultural History, by David S. New. McFarland and Company, 2012. 265pp. Pb. $35.00. ISBN-13: 9780786470587.